Failure analysis of high-strength steel wire under random corrosion. (October 2021) - Xue, Songling; Shen, Ruili; Xue, Huajuan; Zhu, Xiaoxiong; Wu, Qiong; Zhang, Sheng
Abstract: Given the randomness of corrosion and the variability of the constitutive model under corrosion conditions, the high-strength steel wire is selected as the basic component, and the constitutive model of steel wire is obtained through the tensile test of high-strength steel wire under different corrosion degrees. The innovation of this paper is the generation of random corrosion pits in numerical simulations. The random corrosion model of steel wire is developed by python, and the constitutive model of steel wire under different corrosion degrees is developed by FORTRAN, which is embedded in ABAQUS. The failure modes of high-strength steel wire under different random corrosion were analyzed. The results show that corrosion has little effect on elastic modulus and yield strength of steel wire. The ultimate strength and fracture strain of steel wire are decreased due to corrosion. The steel wire becomes brittle, and the breaking force is greatly reduced.